Interventional‐ and amputation‐stage muscle proteomes in the chronically threatened ischemic limb. Issue 1 (24th January 2022) - Ryan, Terence E.; Kim, Kyoungrae; Scali, Salvatore T.; Berceli, Scott A.; Thome, Trace; Salyers, Zachary R.; O'Malley, Kerri A.; Green, Thomas D.; Karnekar, Reema; Fisher‐Wellman, Kelsey H.; Yamaguchi, Dean J.; McClung, Joseph M.
Abstract: Background: Despite improved surgical approaches for chronic limb‐threatening ischemia (CLTI), amputation rates remain high and contributing tissue‐level factors remain unknown. The purpose of this study was twofold: (1) to identify differences between the healthy adult and CLTI limb muscle proteome, and (2) to identify differences in the limb muscle proteome of CLTI patients prior to surgical intervention or at the time of amputation. Methods and results: Gastrocnemius muscle was collected from non‐ischemic controls (n = 19) and either pre‐interventional surgery (n = 10) or at amputation outcome (n = 29) CLTI patients. All samples were subjected to isobaric tandem‐mass‐tag‐assisted proteomics. The mitochondrion was the primary classification of downregulated proteins (> 70%) in CLTI limb muscles and paralleled robust functional mitochondrial impairment. Upregulated proteins (> 38%) were largely from the extracellular matrix. Across the two independent sites, 39 proteins were downregulated and 12 upregulated uniformly. Pre‐interventional CLTI muscles revealed a robust upregulation of mitochondrial proteins but modest functional impairments in fatty acid oxidation as compared with controls. Comparison of pre‐intervention and amputation CLTI limb muscles revealed mitochondrial proteome and functional deficits similar to that between amputation and non‐ischemic controls. Interestingly, these observed changes occurred despite 62% of the amputation CLTI patients having undergone a prior surgical intervention. Conclusions: The CLTI proteome supports failing mitochondria as a phenotype that is unique to amputation outcomes. The signature of pre‐intervention CLTI muscle reveals stable mitochondrial protein abundance that is insufficient to uniformly prevent functional impairments. Taken together, these findings support the need for future longitudinal investigations aimed to determine whether mitochondrial failure is causally involved in amputation outcomes from CLTI. Abstract : Proteomic analyses of CLTI muscle specimens identify a distinct limb muscle proteome signature characterized by a severe mitochondriopathy in amputation‐stage specimens, which was discovered to differ from non‐PAD controls and CLTI pre‐surgical intervention limb muscles. Coincident with the proteome signature, mitochondrial function was severely impaired in amputation‐stage CLTI specimens. Compared to non‐PAD controls, interventional‐stage CLTI specimens displayed an upregulation of the mitochondrial proteome; however, this did not afford any improvement in mitochondrial oxidative phosphorylation.